Development of a Ternary Solid Dispersion Formulation of LW6 to Improve the In Vivo Activity as a BCRP Inhibitor: Preparation and In Vitro/In Vivo Characterization - Rajiv Bajracharya; Sang Hoon Lee; Jae Geun Song; Minkyoung Kim; Kyeong Lee; Hyo-Kyung Han (MDPI AG, 2019)
LW6 (3-[2-(4-adamantan-1-yl-phenoxy)-acetylamino]-4-hydroxy-benzoic acid methyl ester) is a potent inhibitor of drug efflux by the breast cancer resistance protein (BCRP). However, its poor aqueous solubility leads to low bioavailability, which currently limits in vivo applications. Therefore, the present study aimed to develop ternary solid dispersion (SD) formulations in order to enhance the aqueous solubility and dissolution rate of LW6. Various SDs of LW6 were prepared using a solvent evaporation method with different drug/excipient ratios. The solubility and dissolution profiles of LW6 in different SDs were examined, and F8-SD which is composed of LW6, poloxamer 407, and povidone K30 at a weight ratio of 1:5:8 was selected as the optimal SD. The structural characteristics of F8-SD were also examined using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD), and scanning electron microscopy (SEM). In the acidic to neutral pH range, F8-SD achieved rapid dissolution with a drug release of 76−81% within 20 min, while the dissolution of pure LW6 was negligible. The XRPD patterns indicated that F8-SD probably enhanced the solubility and dissolution of LW6 by changing the drug crystallinity to an amorphous state, in addition to the solubilizing effect of the hydrophilic carriers. Furthermore, F8-SD significantly improved the oral bioavailability of topotecan, which is a BCRP substrate, in rats. The systemic exposure of topotecan was enhanced approximately 10-fold by the concurrent use of F8-SD. In conclusion, the ternary SD formulation of LW6 with povidone K30 and poloxamer 407 appeared to be effective at improving the dissolution and in vivo effects of LW6 as a BCRP inhibitor.